Trends in mRNA vaccine research - Szabo, Gabor Tamas (Trends in drug discovery, 2025)
The authoritative guide to the revolutionary concept behind the successful Covid-19 vaccines In Trends in mRNA Vaccine Research, a team of distinguished researchers delivers a practical and up-to-date discussion of the biochemical and biomedical foundations of mRNA vaccines. They also explore the manufacturing conditions required for successful vaccine development and review recent progress in a variety of medical fields, including vaccines against pathogens like SARS-CoV-2, HIV, plasmodium, Mycobacterium tuberculosis, as well as anticancer vaccines. Volume highlights include: - A historical overview of mRNA vaccine development- Immune responses to modified or unmodified mRNA vaccines- A description of the different mRNA vaccine platforms- Latest data on current mRNA vaccine developments against infectious diseases and cancerPerfect for medicinal chemists, immunologists, and epidemiologists, Trends in mRNA Vaccine Research will also benefit researchers and scientists working in the pharmaceutical industry, as well as cancer researchers with an interest in vaccine development